Towards collaborative contract management in public works in Perú: implementation proposals - Campos Medina, Alexander (2020)
This paper proposes the elaboration and application of a protocol of collaborative management within the current legal framework for public works in Peru, in order to expedite the execution and achievement of projects. For this purpose, firstly, it is necessary to analyze what collaborative approach means within the construction industry and why it is necessary for public works based on industry’s best practices. Secondly, to identify challenges on the application of a collaborative approach and tools from the public procurement law that enable this approach. Finally, this paper shares recommendations and conclusions to take into consideration for the elaboration and application of this model.